THE INFLUENCE OF OWNERSHIP STRUCTURE AND DEBT POLICY ON DIVIDEND POLICIES IN MANUFACTURING COMPANIES IN INDONESIA (PERIOD 2016-2018) - Yuniati, Novita (IJMA (Indonesian Journal of Management and Accounting), 2021)
One of the important issues in the world of financial management is related to dividend policy. Various kinds of obstacles can occur so that the company cannot distribute dividends to shareholders. Dividend policy is a company policy to determine which profits earned at the end of the year will be distributed or retained. The purpose of this study was to determine the effect of institutional ownership structure, managerial ownership, and debt policy on dividend policies in manufacturing companies listed on the Indonesia Stock Exchange for the 2016- 2018 period. This type of research is quantitative research. The data taken is an annual report for each independent and dependent variable. The sample selection technique used purposive sampling method and the research data were obtained from 27 companies. The data used is secondary data with the method of collecting documentation data sourced on the Indonesia Stock Exchange in the 2016-2018 observation period. The analytical method used is descriptive analysis and multiple linear regression analysis using the SPSS version 22 program. The results of this study indicate that institutional ownership has a positive and significant effect on dividend policy, managerial ownership has a positive and significant effect on dividend policy, while debt policy has no effect on dividend policy. dividend. The results of the F test obtained the calculated F value of 6.852 with a sig. of 0.000, which means that the independent variables of institutional ownership, managerial ownership and debt policy have a simultaneous effect on dividend policy. The value of Adjusted R Square is 0.180, this means that dividend policy is influenced by 18% institutional ownership, managerial ownership and debt policy, while the remaining 82% is explained by other variables not included in the research model